Efeito da terapia Reiki sobre os índices da variabilidade da frequência cardíaca em pacientes diabéticos - Canella, Glauco César da Conceição [UNESP] (2015)
Evidence on the clinical and physiological effects of bioenergetic therapies lack of scientific studies, particularly those that analyze the risk factors for epidemic diseases such as diabetes. Objectives: To investigate the acute effects of therapeutic intervention Reiki on heart rate variability in individuals between 58 to 75 years with diabetes mellitus type 2. Methodology: A total of 7 individuals of both sexes, aged between 58 and 75 years, type 2 diabetes mellitus Reiki was applied for 50 minutes at this stage were performed the registration of HR and R-R intervals (R-Ri) and calculated indexes of heart rate variability (HRV) in time domain and frequency. Results: The HRV indexes showed no significant differences between the rest condition, placebo and Reiki, to points 1, 2, 3 and 4 (p> 0.05). Conclusions: The application of Reiki do not change the temporal and spectral indices of cardiac autonomic modulation.